Enhancing Child-Friendly Environments in Urban Villages Through Spatial Transformation Strategies in Foshan China - Yongming, Yang; Raja Nur Syaheeza, Raja Mohd Yazit; Julaihi, Wahid; Mervyn Wong, Hsin Jyi (JISEM, 2025)
The rapid urbanization of Foshan, China leads to insufficient development of child-friendly environments because urban villages undergo planning deficits alongside limited spatial capabilities. The research explores spatial transformation methods to create more child-friendly environments inside Foshan urban neighborhood areas by assessing independent movement and diverse play opportunities and local resident participation. Our research involved a mixed-methods evaluation of the five villages Shiken, Nanyue, Poyang, Shiliang and Dongpo through spatial mapping, 180 hours of behavioral observations (n = 565), 98 caregiver surveys along with participatory workshops (n = 125). Shiliang emerges as most child-friendly (mean score: 3.77 standard deviation: 0.28) because of its excellent facilities efficient recreational facilities (park coverage exceeds 85% within a 400m radius) combined with high safety ratings (mean score: 3.4) whereas Nanyue stands out as least child-friendly (mean score: 2.42 standard deviation: 0.32) because of its high traffic risks (vehicle density of 12 vehicles per 100 meters of distance). The strength of relationship between park facilities availability and actual usage was 0.77 at a significance level p < 0.01 and vehicle density showed a negative correlation of -0.69 with park safety at p < 0.01. We suggest establishing a complete framework which combines physical space redesign such as larger sidewalks with play areas of different kinds and active involvement of children together with their caregivers for ownership development. The research enhances child-friendly urban planning through an investigation that unites physical and social aspects while presenting applicable guidelines for worldwide urban villages.